SEMANTIC MOTIVATION (Modern education and development, 2025)
This article discusses semantic motivation in English, examining how word meanings relate to their structure and usage. It distinguishes between motivated, non-motivated, and partially motivated words, highlighting the roles of metaphor, metonymy, and culture. Examples like foot of the mountain and keyboard illustrate key points. The article also notes how meanings can change over time through historical and social factors.